1983
DOI: 10.1002/mpo.2950110206
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytosis X in children: Patterns of disease and results of treatment

Abstract: The pathologic materials and clinical courses of 36 children aged 1 month-22 years, with histiocytosis X (H-X) seen at the Philadelphia Children's Cancer Research Center from 1970 to 1979 were reviewed. The pathologic subtype of H-X was favorable (type II) in 31 patients, unfavorable (type I) in one patient, and unclassified in four patients whose specimens were limited to a skin biopsy. Sixteen patients had localized H-X involving bone (14 patients), soft tissue (1 patient), or skin only (1 patient); all are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…No statistically significant association was found be- tween LCH and the use of antibiotics, tranquilizers, anti-is similar to that of other reported case series [21,22]. hypertensives, anti-inflammatory agents, hormones, al-Moreover, as in other reports [4][5][6], LCH cases demonlergy medication, oral contraceptives, and recreational strated a slight male predominance, and appeared to be drugs.…”
Section: Infancysupporting
confidence: 90%
“…No statistically significant association was found be- tween LCH and the use of antibiotics, tranquilizers, anti-is similar to that of other reported case series [21,22]. hypertensives, anti-inflammatory agents, hormones, al-Moreover, as in other reports [4][5][6], LCH cases demonlergy medication, oral contraceptives, and recreational strated a slight male predominance, and appeared to be drugs.…”
Section: Infancysupporting
confidence: 90%
“…These factors have been successfully applied with some variations in different institutions [1][2][3][4]9,14,20]. They generally correlated with disease outcome, but failed to clearly discriminate patients with very poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Histiocyte Society defined two categories for a uniform description of the disease extent, namely ''single system'' LCH (SS-LCH) and ''multisystem'' LCH (MS-LCH) [12]. SS-LCH is usually associated with a favorable prognosis [1,[13][14][15]. MS-LCH, however, has an extremely variable clinical course and unpredictable prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…tients were excluded from this review because of inadequate specimens or incorrect diagnosis, as previously reported [2]. Five additional patients were excluded from analysis of treatment results because of inadequate initial radiographic studies of the bony skeleton (three patients) or lack of any follow-up information (two patients).…”
Section: Introductionmentioning
confidence: 99%